The Strength of Proof of Notary Deeds Made Electronically in E-Commerce Transactions in the Indonesian Legal System - Rohmaniah, Sanivatun; Adillah, Siti Ummu (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The development of Information and Communication Technology has brought significant positive impacts in various fields of human life today. The various conveniences offered by the development of telecommunications have made it possible for human relations to take place quickly and easily without taking into account the aspects of space and time. Legal certainty can be achieved if there are no conflicting provisions between one law and another. Obstacles experienced in making Electronic Notary Deeds in e-commerce transactions, among others, in terms of legal substance, namely the absence of specific legal certainty that further regulates the application of information and communication technology in making Notary Deeds, in terms of legal structure, namely there is no structure good law, it will be an obstacle for a Notary to carry out his authority in making deeds electronically and in terms of legal culture, namely the development of existing technology, until now it has not been adapted to the legal culture of Indonesian society. The solution in proving the Notary Deed Electronically in E-Commerce Transactions is that when viewed from a juridical perspective, the actions that can be taken are to revise UUJN and ITE.Keywords: Commercial; Electronic; Verification.